Atmospheric PCDD/PCDF emission inventory for Turkey - Saral, Arslan; Gunes, Gulten; Demir, Selami (TURKISH NATL COMMITTEE AIR POLLUTION RES & CONTROL-TUNCAP, 2014)
While studies related to national emission inventories for polychlorinated dibenzo-p-dioxins (PCDD) and furans (PCDF) form the first steps of worldwide elimination of these pollutants, consistency between the methodologies applied for emission estimation is of great importance in the aspect of monitoring the changes in emissions. This study presents PCDD/PCDF emission inventory for Turkey estimated using a standardized toolkit developed by UNEP Chemicals. The total emission rate in Turkey was estimated as 723 g I-TEQ yr(-1). For those source categories without enough information on air pollution control equipment, emissions were calculated as 1 873 g I-TEQ yr(-1) using the highest emission factors to represent the worst-case conditions. Ferrous-and-nonferrous metal production was ranked first with emissions ranging from 583 g I-TEQ yr(-1) (min) to 1 419 g I-TEQ yr(-1) (max). Other important source categories were determined to be coal burning for residential heating and mineral product manufacturing using fossil fuels with emissions of 38 g I-TEQ yr(-1) and 3.65 g I-TEQ yr(-1), respectively. The contribution of ferrous-and-nonferrous metal production to the total emission ranged from 76% (min) to 81% (max). In contrast to other industrialized countries, PCDD/PCDF emissions from waste combustion plants were found to be negligible in Turkey.
Keywords: Turkey; emission inventory; PCDD/PCDF; POPs; DIBENZO-P-DIOXINS; DEPOSITION; RELEASE; PCDFS; PCDDS; Environmental Sciences & Ecology